2015
DOI: 10.1080/19476337.2015.1067646
|View full text |Cite
|
Sign up to set email alerts
|

Structure and property changes of soybean protein isolates resulted from the glycation and cross-linking by transglutaminase and a degraded chitosan

Abstract: Structure and property changes of soybean protein isolates resulted from the glycation and cross-linking by transglutaminase and a degraded chitosan Cambios en la estructura y en las propiedades del aislado de proteína de soja como resultado de la glicación y reticulación mediante transglutaminasa y chitosán degradado A glycated and cross-linked soybean protein isolate (GC-SPI) with the glucosamine content of 19.40 g/kg protein was prepared by using SPI, transglutaminase, and a degraded chitosan under fixed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, the application remains substantially limited due to the high-water sensitivity, undesirable processability, and inferior mechanical strength [36]. A lot of investigations on modification of SPI have been carried out to solve the problems mentioned above [37,38,39]. In our previous work, a series of crosslinked membranes was prepared by SPI crosslinked with ethylene glycol diglycidyl ether (EGDE) as the crosslinker and it was found that the crosslinked structure could improve the water resistance of SPI/EGDE membrane, but it also reduced the ionic conductivity of the pure SPI film and electrochemical performance of the supercapacitor [40].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application remains substantially limited due to the high-water sensitivity, undesirable processability, and inferior mechanical strength [36]. A lot of investigations on modification of SPI have been carried out to solve the problems mentioned above [37,38,39]. In our previous work, a series of crosslinked membranes was prepared by SPI crosslinked with ethylene glycol diglycidyl ether (EGDE) as the crosslinker and it was found that the crosslinked structure could improve the water resistance of SPI/EGDE membrane, but it also reduced the ionic conductivity of the pure SPI film and electrochemical performance of the supercapacitor [40].…”
Section: Introductionmentioning
confidence: 99%
“…IgE and IgG antibodies produced by allergic individuals can specifically recognise linear or conformational epitopes exhibited by the allergen molecule. Zhu et al (2015) suggested that a lower in vitro digestibility of soy protein isolate (SPI) was observed after incubated with MTG and a degraded chitosan. Zhu et al (2015) suggested that a lower in vitro digestibility of soy protein isolate (SPI) was observed after incubated with MTG and a degraded chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a main characteristic of many food allergens is the resistance to gastric digestion, and digestibility analysis has been regarded as an important method to evaluating the allergenic potential of protein (Lang et al, 2015). Zhu et al (2015) suggested that a lower in vitro digestibility of soy protein isolate (SPI) was observed after incubated with MTG and a degraded chitosan. Therefore, it is necessary to evaluate the effect of MTG-induced modifications on the digestibility and immunoreactivity of glycinin.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Álvarez, Fernández, and Canet (2009) and Fernández, Canet, and Alvarez (2009) reported that the addition of kappa-carrageenan (κ-C) and xanthan gum (XG) at a low concentration (1.5 g/kg) to MP could improve the overall acceptability (OA) and minimize damage arising from freezing and thawing. Additionally, the effect of soybean protein isolate (SPI), which contains 90% protein and usually used in the food industry (Zhu, Liu, Fu, & Zhao, 2016), on physicochemical, functional and sensory characteristics of MP products has been reported. Obtained results showed that SPI concentrations had a significant impact on rheological properties of MP (Álvarez, Fernández, Olivares, & Canet, 2012).…”
Section: Introductionmentioning
confidence: 99%